Students Perception on Landscape in UTHM Main Campus - Ishak, Nuruaini; Masram, Haidaliza; Md Yassin, Azlina (Research in Management of Technology and Business, 2020)
Landscape mainly function as an activity that add value in the aesthetic quality of the natural and built environment also for the social well being of a community. Although campus landscape plays an important role in student’s lifestyle, landscape provision within Universiti Tun Hussein Onn Malaysia (UTHM) main campus is not comprehensive and left much to be desired. Considering the significant of landscaping in enhancing students wellbeing, a study is conducted to identify importance of landscape to students, and evaluate the condition of the existing landscape within the campus and to study the student’s needs for landscape. Data and information were obtained through interviews, questionnaires and observation. For the questionnaire, a total of 224 students participated in this study and the interview was conducted with the Pembangungan dan Pengurusan Hartabina (PPH). The researcher carried out observation the study areas such as roadsides, parking, recreation areas and buildings as evidence by taking photos around to support the findings. The results indicate that landscape provision is important to enhance students’ quality of life in campus. However, the existing condition of landscape in UTHM main campus is still unsatisfactory and there is a need for some improvement. Improvements could refer to student’s recommendation that was identified. Overall, there are much improvements to be made for the hardscape and softscapes that are still lacking. Findings and recommendations of this study is expected to guide all parties involved as well as encourage physical development in the main campus especially in landscape provision.